Optimal management of markets for bankable emission permits - Jussi Lintunen; Olli-Pekka Kuusela (Fondazione Eni Enrico Mattei (FEEM), 2015)
We examine the optimal management of emission permit markets when banking but not borrowing of permits is allowed. The regulator maximizes expected social welfare through an optimal allocation rule in an infinite horizon setting. The policy is second-best as the emission cap is set before the uncertainty about the current state of the economy is resolved. In this setting, the role of banking is to decrease the regulator's risk as it generates an endogenous price floor in the permit markets. We show that the regulator's optimal policy adjusts the emissions cap irrespective of the existing number of permits in the bank, with the implication that the regulator neutralizes the effect of the existing bank on future permit prices. We derive the optimality conditions for the second-best emission cap with banking and solve the model analytically in the case of IID shocks. Our results show that the discount factor together with the slopes of the marginal damages and benefits determine the welfare gains from allowing baking of permits. Finally, to address the current state of the EU Emission Trading Scheme (EU ETS) and guide the design of future permit markets, we solve the model numerically with persistent shock process and show that the optimal emission cap is positively correlated with business cycles, meaning that during downturns the regulator should tighten the cap. The expected emissions and permit prices also correlate positively with economic activity.
Keywords: E32; Q54; Q58; 330; Cap and Trade; Climate Change; Business Cycle; Second Best; Prices vs. Quantities